Efisiensi pemeliharaan taman: studi kasus di hotel the Oberoi, Bali - Pranata, I Nyoman Darma; Sudarsana, Anak Agung Gede Dalem; Mayadewi, Ni Nyoman Ari (Jurnal Arsitektur Lansekap, 2018)
Gardening efficiency: case study in the Oberoi Hotel, Bali. Bali is one of the very famous international tour destination around the world. One important element of tourism is accommodation as a rest area. Hotel The Oberoi Bali is one of the five stars hotel as accommodations in Bali. Hotel The Oberoi Bali has six hectare land with 60% of outdoor area and 40% of building area. This study aims to find the efficiency of the park keepers in Hotel The Oberoi Bali. The method that used in this study is survey method, with observation techniques interview, literature review and questionnaire. Based on the result of the research, it is found that the maintenance system which is applied is the maintenance system of the unit or zone, and the special maintenance system, the work capacity is done on sweeping or paving and grass pruning with thrust machine, less work in watering activities using sprinklers and plastic hoses, pruning bushes and ground cover with pruned shears. Recommendation of maintenance schedule in writing, reward system for garden staff to improve work efficiency and training which can increase knowledge and skill in maintenance activities for labor.